Visual Discovery Learning with Canva to Enhance Science Understanding and Self Regulated Learning - Putri Hilma Rizkiah; Asep Samsudin; Wahyu Hidayat (Elementary Teacher Education Program, Majalengka University, 2026)
This study was motivated by the low level of students’ science conceptual understanding and self regulated learning in elementary schools, indicating the need for more effective and meaningful instructional innovations. The study aimed to develop a Canva-assisted Discovery Learning model to improve both aspects. A quantitative descriptive method was employed using a Research and Development (R&D) approach adapted from Borg and Gall, which included preliminary study, product development, expert validation, limited trials, and field testing. The participants were 56 elementary school students. The instruments consisted of expert validation sheets, a conceptual understanding test, and a self-regulated learning observation sheet. Data were analyzed using reliability and normality tests, followed by a paired sample t-test for normally distributed conceptual understanding data and a Wilcoxon test for non-normally distributed self regulated learning data. Learning improvement was further examined using N-gain analysis. The results showed that the developed model had high validity and was suitable for implementation. In addition, there was a significant improvement in students’ science conceptual understanding (N-gain = 0.34; moderate category; p < 0.05) as well as in their self-regulated learning (p < 0.05). Therefore, the Canva-assisted Discovery Learning model is effective as an interactive, contextual, and student-centered approach to science learning.